2017
DOI: 10.1159/000456583
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Discoveries Highlight Environmental Factors as Key Drivers of Liver Disease

Abstract: Background: Over the last 50 years, genetic studies have uncovered a spectrum of rare and common alleles that confer susceptibility to both Mendelian and complex forms of liver disease. For disorders of Mendelian inheritance, identification of the causal variants has demonstrated that common environmental exposures can elicit severe liver pathogenesis in predisposed individuals. Specific environmental triggers for complex liver disorders are largely unknown; however, large-scale association studies indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 107 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…The identity of such environmental risk factors is poorly known beyond the potential protective effects of smoking and coffee. [13][14][15][16][17] Among the many potential exogenous factors impacting PSC pathogenesis, 18 the gut microbiota, the collective community of all microorganisms in the gastrointestinal tract, has more recently received the major attention (►Fig. 1).…”
mentioning
confidence: 99%
“…The identity of such environmental risk factors is poorly known beyond the potential protective effects of smoking and coffee. [13][14][15][16][17] Among the many potential exogenous factors impacting PSC pathogenesis, 18 the gut microbiota, the collective community of all microorganisms in the gastrointestinal tract, has more recently received the major attention (►Fig. 1).…”
mentioning
confidence: 99%
“…This particularly relates to GWAS studies focused on complex diseases. Examples in the liver context are PBC (115 associations and 8 studies) and PSC (308 associations and 17 studies), in which most of the identified disease variants appeared at a very low effect size, suggesting a marginal genetic contribution in respect to other risk factors (i.e., environmental) at play (10,11).…”
Section: Genomicsmentioning
confidence: 99%